BS EN 15502-2-1. Gas-fired central heating boilers. Part 2-1. Specific standard for type C appliances and type B2, B3 and B5 appliances of a nominal heat input not exceeding 1 000 kW (5th August 2021) - British Standards Institution,
No abstract available